Combination Therapies Including Cilofexor and Firsocostat for Bridging Fibrosis and Cirrhosis Attributable to NASH. Issue 2 (15th February 2021) - Loomba, Rohit; Noureddin, Mazen; Kowdley, Kris V.; Kohli, Anita; Sheikh, Aasim; Neff, Guy; Bhandari, Bal Raj; Gunn, Nadege; Caldwell, Stephen H.; Goodman, Zachary; Wapinski, Ilan; Resnick, Murray; et al.
Abstract : Background and Aims: Advanced fibrosis attributable to NASH is a leading cause of end‐stage liver disease. Approach and Results: In this phase 2b trial, 392 patients with bridging fibrosis or compensated cirrhosis (F3‐F4) were randomized to receive placebo, selonsertib 18 mg, cilofexor 30 mg, or firsocostat 20 mg, alone or in two‐drug combinations, once‐daily for 48 weeks. The primary endpoint was a ≥1‐stage improvement in fibrosis without worsening of NASH between baseline and 48 weeks based on central pathologist review. Exploratory endpoints included changes in NAFLD Activity Score (NAS), liver histology assessed using a machine learning (ML) approach, liver biochemistry, and noninvasive markers. The majority had cirrhosis (56%) and NAS ≥5 (83%). The primary endpoint was achieved in 11% of placebo‐treated patients versus cilofexor/firsocostat (21%; P = 0.17), cilofexor/selonsertib (19%; P = 0.26), firsocostat/selonsertib (15%; P = 0.62), firsocostat (12%; P = 0.94), and cilofexor (12%; P = 0.96). Changes in hepatic collagen by morphometry were not significant, but cilofexor/firsocostat led to a significant decrease in ML NASH CRN fibrosis score ( P = 0.040) and a shift in biopsy area from F3‐F4 to ≤F2 fibrosis patterns. Compared to placebo, significantly higher proportions of cilofexor/firsocostat patients had a ≥2‐point NAS reduction; reductions in steatosis, lobular inflammation, and ballooning; and significant improvements in alanine aminotransferase (ALT), aspartate aminotransferase (AST), bilirubin, bile acids, cytokeratin‐18, insulin, estimated glomerular filtration rate, ELF score, and liver stiffness by transient elastography (all P ≤ 0.05). Pruritus occurred in 20%‐29% of cilofexor versus 15% of placebo‐treated patients. Conclusions: In patients with bridging fibrosis and cirrhosis, 48 weeks of cilofexor/firsocostat was well tolerated, led to improvements in NASH activity, and may have an antifibrotic effect. This combination offers potential for fibrosis regression with longer‐term therapy in patients with advanced fibrosis attributable to NASH.